Managing the dimensions of relationship marketing in the food service industry - Firdaus Abdullah,; Agnes Kanyan, (Penerbit Universiti Kebangsaan Malaysia, 2013)
The present paper proposes a new instrument for measuring relationship marketing that is uniquely designed for the foodservice industry. In particular, the underlying dimensions of relationship marketing as perceived by customers are identified. The proposed 31-item instrument is empirically tested for unidimensionality, reliability and validity using both exploratory and confirmatory factor analyses. A factorial analysis suggests that relationship marketing is a multidimensional construct consisting of four key dimensions: trust, communication, empathy and commitment. A subsequent multiple regression analysis reveals that all of the dimensions are positively correlated with customer loyalty and trust is the most important dimension.